ASSESSMENT OF THE CONCENTRATION OF HEAVY METALS IN ELECTRONIC WASTE DUMP SITE IN ALABA INTERNATIONAL MARKET, LAGOS STATE (FUDMA JOURNAL OF SCIENCES, 2024)
This research investigates the concentration of heavy metals (Pb, Cu, Cd, and Ni) at e-waste dump sites in Lagos, Nigeria. Measuring the concentration and distribution of heavy metals across different soil depths and comparing these concentrations in soil and water samples. For this purpose, 78 soil samples were taken from different sampling points, and analyses were carried out following standard procedures. The soil samples retrieved from the e-waste site consistently exhibit a sandy soil texture, as per the USDA classification system. It was found that Cu generally has the highest concentrations in the soil layers (2022.20-2312.67mgkg-1) while Cd generally has the least (16.32-22.62 mgkg-1). The elements observed for this study are Cu > Pd >Ni > Cd. Overall, this comprehensive study provides valuable insights into the environmental contamination and health risks posed by e-waste dump sites, emphasizing the need for effective management strategies to mitigate these risks and protect human health and the environment.
Keywords: Soil contamination; Pollution; Heavy metals; Electronic waste; Alaba International Lagos; Nigeria